Canine Splenic Nodular Lymphoid Lesions: Immunophenotyping, Proliferative Activity, and Clonality Assessment. Issue 5 (September 2018) - Sabattini, Silvia; Lopparelli, Rosa Maria; Rigillo, Antonella; Giantin, Mery; Renzi, Andrea; Matteo, Chiara; Capitani, Ombretta; Dacasto, Mauro; Mengoli, Marisa; Bettini, Giuliano
Canine splenic lymphoid nodules are currently classified as indolent lymphomas (marginal zone lymphoma [MZL], mantle cell lymphoma [MCL]) or nodular hyperplasia (lymphoid [LNH] or complex [CNH] type). Their differentiation can be difficult on morphology, because of similar histologic appearance and poorly defined diagnostic criteria. Thirty-five surgical samples of splenic lymphoid nodules were reviewed in order to assess the diagnostic contribution of immunophenotyping, proliferative activity and clonality (PARR) in differentiating between hyperplastic and neoplastic lesions. Proliferative activity was evaluated by double immunolabeling for Ki-67 and CD79a, in order to separately assess the proliferative activity of B cells and non-B cells. Definitive diagnoses were MZL ( n = 11), MCL ( n = 4), LNH ( n = 10), and CNH ( n = 10). The overall concordance between histology and PARR was above 90%. Lymphomas had a significantly higher percentage of CD79a-positive areas (mean, 36.30%; P = .0004) and a higher B-cell proliferative activity (median Ki-67 index, 5.49%; P = .0012). The threshold value most accurately predicting a diagnosis of lymphoma was ≥28% of B-cell areas, with a Ki-67 index above 3%. Dogs were monitored for a median follow-up time of 870 days (IQR, 569-1225), and no relapses were documented. Overall median survival time was 1282 days. The combination of histology, immunohistochemistry and PARR can improve the diagnostic accuracy for canine splenic lymphoid nodules, although the long-term behavior of these lesions appears similar.